2021
DOI: 10.3390/nu13072424
|View full text |Cite
|
Sign up to set email alerts
|

Eating Dinner Early Improves 24-h Blood Glucose Levels and Boosts Lipid Metabolism after Breakfast the Next Day: A Randomized Cross-Over Trial

Abstract: Aim To examine whether mild early time-restricted eating (eating dinner at 18:00 vs. at 21:00) improves 24-h blood glucose levels and postprandial lipid metabolism in healthy adults. Methods Twelve participants (2 males and 10 females) were included in the study. In this 3-day (until the morning of day 3) randomized crossover study, two different conditions were tested: eating a late dinner (at 21:00) or an early dinner (at 18:00). During the experimental period, blood glucose levels were evaluated by each par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
(49 reference statements)
1
11
1
Order By: Relevance
“…By comparison, the natural progression of fasting glucose in the general non-diabetic population is a rate of 0.04–0.06 mmol/L per 10 years of age [ 25 ]. Our findings on insulin sensitivity are consistent with prior studies that observed that eating earlier in the day was associated with beneficial metabolic outcomes, including insulin sensitivity [ 26 , 27 , 28 ]. In addition, a randomized cross-over study tested the impact of earlier timing of lunch (13:00) to a later lunch time (16:30) over one week and found that the earlier lunchtime was associated with greater glucose tolerance and greater fasting carbohydrate oxidation [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…By comparison, the natural progression of fasting glucose in the general non-diabetic population is a rate of 0.04–0.06 mmol/L per 10 years of age [ 25 ]. Our findings on insulin sensitivity are consistent with prior studies that observed that eating earlier in the day was associated with beneficial metabolic outcomes, including insulin sensitivity [ 26 , 27 , 28 ]. In addition, a randomized cross-over study tested the impact of earlier timing of lunch (13:00) to a later lunch time (16:30) over one week and found that the earlier lunchtime was associated with greater glucose tolerance and greater fasting carbohydrate oxidation [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…[39] Garaulet et al [40] also demonstrated in overweight/obese adults consuming a Mediterranean diet-whereby lunch constituted the highest daily energy distribution, that volunteers consuming an earlier lunch (before 3 pm) lost significantly more weight than those with a later lunch (after 3 pm). Another recent study by Nakamura et al [41] reported that eating dinner 3 h earlier (at 6 pm versus 9 pm) significantly improved 24-h glycemic response and increased lipid oxidation after the next breakfast, in healthy adults. However, a recent study questioned the effectiveness of early and late scheduling of meals as per the larger body of evidence.…”
Section: Energy Intake Distribution Throughout the Daymentioning
confidence: 93%
“…Another recent study by Nakamura et al. [ 41 ] reported that eating dinner 3 h earlier (at 6 pm versus 9 pm) significantly improved 24‐h glycemic response and increased lipid oxidation after the next breakfast, in healthy adults. However, a recent study questioned the effectiveness of early and late scheduling of meals as per the larger body of evidence.…”
Section: Dietary Components Intake Timing and Their Interaction With ...mentioning
confidence: 99%
“…We identified eight studies in which energy expenditure was measured in response to acute TRE [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. TRE can be categorized based on when the eating window occurs, that is early TRE (eating earlier in the day), midday TRE (eating in the middle of the day) and late TRE (eating later in the day).…”
Section: Effects Of If On Energy Metabolism: Energy Expenditure and S...mentioning
confidence: 99%
“…A total of seven studies reported substrate oxidation in response to acute TRE [ 84 , 85 , 86 , 87 , 88 , 89 , 90 ], providing mixed findings. In general, TRE, regardless of the time of the eating window, does not appear to acutely affect 24 h substrate oxidation [ 84 , 85 , 86 , 87 , 88 , 93 ].…”
Section: Effects Of If On Energy Metabolism: Energy Expenditure and S...mentioning
confidence: 99%